THE OWNERSHIP RIGHTS OF ABANDONED LAND ACCORDING TO LAW NO. 5 OF 1960 CONCERNING THE BASIC AGRARIAN PRINCIPLES IN THE PERSPECTIVE OF ISLAMIC LAW - Al Anawiyah, Siti (Journal of Scientech Research and Development, 2024)
Indonesia is an agricultural country, where approximately 70% of the population in Indonesia works in the agricultural sector, but in fact not all farmers have their own agricultural land to manage, therefore providing human resources in the agricultural sector is very important. Judging from Islamic rules, if there is a plot of land that has not been managed or abandoned by the owner, then the land has the status of unowned land which can then give rise to new laws, namely that it can be assessed by other parties using methods to function, revive the land (Ihyā Al -Mawat). This research aims to determine the terms and conditions of ownership rights to abandoned land in UUPA no. 5 of 1960 and how to have rights to abandoned land according to UUPA from the perspective of Islamic principles. This type of research is library research, using a normative juridical approach. Ownership rights to abandoned land according to the Basic Agrarian Law Number 5 of 1960, can be obtained through land reform based on Article 17 paragraph 3 of the UUPA, then by the mechanism specified in the Regulation of the Head of the Land Agency. Land Band Number 5 of 2011 concerning Procedures for Using Used Land. Abandoned Land. In Islamic law, the study of abandoned land is known as ihya' al mawat, namely reviving dead land, and according to firm opinion, ownership rights require government permission. So that by opening up the abandoned land, the land can be utilized, managed and utilized according to its function.